CNS progression during vinblastine or targeted therapies for high‐risk relapsed ALK‐positive anaplastic large cell lymphoma: A case series. Issue 6 (7th March 2018) - Ruf, Stephanie; Hebart, Holger; Hjalgrim, Lisa Lyngsie; Kabickova, Edita; Lang, Peter; Steinbach, Daniel; Schwabe, Georg C.; Woessmann, Wilhelm
Abstract: Vinblastine and targeted therapies induce remissions in patients with relapsed or progressive anaplastic lymphoma kinase (ALK)‐positive anaplastic large cell lymphoma (ALCL). Central nervous system (CNS) prophylaxis often is not included during re‐induction in CNS‐negative relapse patients. We report on five patients with progressive or early relapsed ALK‐positive ALCL who developed CNS progression during re‐induction with vinblastine, crizotinib, or brentuximab vedotin given for bridging to allogeneic blood stem cell transplantation. These observations suggest that CNS prophylaxis should be considered in ALCL patients suffering progression during initial therapy who receive re‐induction using agents with limited CNS penetration.